Magnetic Tunnel Junction Based on MgO Barrier Prepared by Natural Oxidation and Direct Sputtering Deposition - Chen, Xiaohong; Freitas, Paulo. P. (Nano-Micro Letters, 2012)
Magnetic tunnel junctions (MTJs) based on MgO barrier have been fabricated by sputtering single crystal MgO target and metal Mg target, respectively, using magnetic sputtering system Nordiko 2000. MgO barriers have been formed by a multi-step deposition and natural oxidization of Mg layer. Mg layer thickness, oxygen flow rate and oxidization time were adjusted and the tunnel magnetoresistance (TMR) ratio of optimal MTJs is over 60% at annealing temperature 385°. The (001) MgO crystal structure was obtained when the separation distance between MgO target and substrate is less than 6 cm. The TMR ratio of most MgO based MTJs are over 100% at the separation distance of 5 cm and annealing temperature 340°C. The TMR ratios of MTJs are almost zero when the separation distance ranges from 6 to 10 cm, due to the amorphous nature of the MgO film.